2012
DOI: 10.1016/j.vetmic.2011.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Pre-infection of pigs with Mycoplasma hyopneumoniae modifies outcomes of infection with European swine influenza virus of H1N1, but not H1N2, subtype

Abstract: Swine influenza virus (SIV) and Mycoplasma hyopneumoniae (Mhp) are widespread in farms and are major pathogens involved in the porcine respiratory disease complex (PRDC). The aim of this experiment was to compare the pathogenicity of European avian-like swine H1N1 and European human-like reassortant swine H1N2 viruses in naïve pigs and in pigs previously infected with Mhp. Six groups of SPF pigs were inoculated intra-tracheally with either Mhp, or H1N1, or H1N2 or Mhp+H1N1 or Mhp+H1N2, both pathogens being ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 22 publications
3
31
1
3
Order By: Relevance
“…This was in agreement with the symptoms we observed in similar previous studies [17], [18]. In the present experiment, we showed that feed restriction induced a decrease in rectal temperature that could be caused by a decrease in heat production due to feed digestion [26].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This was in agreement with the symptoms we observed in similar previous studies [17], [18]. In the present experiment, we showed that feed restriction induced a decrease in rectal temperature that could be caused by a decrease in heat production due to feed digestion [26].…”
Section: Discussionsupporting
confidence: 94%
“…Strain isolations, as well as preparation and titration of inocula were performed as previously described [17].…”
Section: Methodsmentioning
confidence: 99%
“…Deblanc et al. () showed that M. hyopneumoniae infection increased the severity of H1N1 SIV but not that of H1N2 SIV. Opriessnig et al.…”
Section: Pathogenicitymentioning
confidence: 99%
“…Viruses that cause respiratory disease and pneumonia in growing pigs include the porcine reproductive and respiratory syndrome virus (PRRSV), swine influenza virus (SIV), pseudorabies virus (PRV), porcine rubulavirus (PorPV), porcine circovirus type-2 (PCV-2), and porcine respiratory coronavirus (PRCV). All these viral agents can act individually or through interaction with each other, and associations with other infectious agents of bacterial origin can also occur (Choi et al, 2003;Deblanc et al, 2012;Grau-Roma and Segales, 2007;Kirkland and Stephano, 2006;Morin et al, 1990;Rivera-Benitez et al, 2013a;Segales et al, 1997). PorPV is the etiological agent of blue-eye disease (BED) in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…The common subtypes circulating in swine have been characterised as H1N1, H1N2, and H3N2 (Brookes et al, 2009;Olsen et al, 2006). SIV has been associated with porcine respiratory disease complex (PRDC) in growing or fattening pigs (10-22 weeks of age), while interactions with Mycoplasma hyopneumoniae, PRRS, and PCV-2 (Deblanc et al, 2012;Van Reeth et al, 1996Yazawa et al, 2004 have been widely studied. There are no previous studies of experimental or natural co-infection of PorPV and SIV.…”
Section: Introductionmentioning
confidence: 99%